Current transport through ohmic contacts to indiume nitride with high defect density - Sai, P.O.; Safriuk, N.V.; Shynkarenko, V.V.; Brunkov, P.N.; Jmerik, V.N.; Ivanov, S.V. (Functional Materials, 2018)
The temperature dependences of contact resistivity are measured for Pd/Ti/Au ohmic contacts toward indium nitride (with different doping level 2.0ċ10¹⁸ and 8.3ċ10¹⁸ cm⁻³) over the wide temperature range (4.2 - 380 K). The growing curves are obtained in the entire investigated temperature range for both doping level. They are explained within the mechanism of thermionic current flow through metal shunts associated with the so-called conducting dislocations. Good agreement between the theoretical and experimental dependences is obtained assuming that the flowing current is limited by total resistance of metal shunts. Moreover the effect of temperature dependence of metal resistivity on total contact resistivity was observed. The density of conducting dislocations obtained from the theory is coherent with the density of screw and edge dislocations obtained from X-ray diffraction investigation of the structure.